2009
DOI: 10.1039/b903603b
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effects on the light-induced C–C and C–Br bond activation in (bisphosphine)(η2-tolane)Pt0 complexes. A TD-DFT study

Abstract: A theoretical study of the steric and electronic effects of different substituents on the electronic ground and excited states of (bisphosphine)(eta2-tolane)Pt0 complexes is presented. A natural-bond-order (NBO) analysis has been performed to describe the bonding nature of the "hapto-like" coordination of the Pt atom to the alkyne bond of the tolane group. The results show an important contribution of the pi-back donation in all complexes, amounting to half of the energy associated to the sigma-bonding interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 18 publications
0
18
0
2
Order By: Relevance
“…In general, it is only the experimental UV absorption spectrum or emission energies that are compared with the theory. Our work on Ru, [197][198][199][200] Ir, [201,202] Pt [203,204] and Zn [205] complexes, and that of many other groups, see for example refs. [206][207][208][209], have found that, astonishingly, TD-DFT can be in reasonable agreement with the experiment as long as a judicious selection of functionals/basis is done and solvent effects are included.…”
Section: Excited-state Description Of Transition Metal Complexesmentioning
confidence: 97%
“…In general, it is only the experimental UV absorption spectrum or emission energies that are compared with the theory. Our work on Ru, [197][198][199][200] Ir, [201,202] Pt [203,204] and Zn [205] complexes, and that of many other groups, see for example refs. [206][207][208][209], have found that, astonishingly, TD-DFT can be in reasonable agreement with the experiment as long as a judicious selection of functionals/basis is done and solvent effects are included.…”
Section: Excited-state Description Of Transition Metal Complexesmentioning
confidence: 97%
“…In the limit f στ xc = 0 and b = 1, the equations above reduce to the TD-HF case. [56][57][58][59][60][61][62][63] Admittedly, the charge-transfer is not long range inter-molecular but intra-molecular in these systems, but questions remain how general these findings are. The singlet-triplet splitting therefore tends to zero and excitation energies reduce to the Kohn-Sham gap.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional organic substituents are extensively investigated due to their importance in tuning the chemical, physicochemical, and biochemical properties of chemical species . Various substituent groups on catalysts ligands result in different catalytic effects, while multiple substituent groups on substrates can also change their reactivities .…”
Section: Introductionmentioning
confidence: 99%